PERILAKU BERALIH MEREK KONSUMEN DALAM MEMBELI HANDPHONE DI KOTA SEMARANNG (Studi kasus di Kecamatan Tembalang Semarang) - Suhroni, Suhroni; Sutopo, Sutopo (Faculty of Economics and Business Diponegoro University, 2015)
Assorted these days handphone product choice many on the market by producer, giving opportunity to consumer to consume with various brand choice. Immeasurable of product brand which on the market to consumer make consumer have opportunity to change over from one brand to other brand. Pursuant to the mentioned, hence this research aim to to identify and analyse influence disgruntled of consumer, characteristic categorize experience and product to the product to decision of transfer of handphone brand. In this research of used by population is all migratory consumer of handphone brand in District of Tembalang Semarang. With technique intake of purposive sampel, with migratory consumer responder criterion of handphone brand in District of minimum Tembalang Semarang have changed handphone brand 2 times, is so that obtained by sampel 100 responder. As for data which is used in this research of primary data which is diproleh from kuesioner. Data analysis use doubled linear regresi. Pursuant to result of research obtained by result of regresi coefficient disgruntled of consumer 0,490 and signifikan level 0,000 < 0,05 so that first hypothesis of ketidakpuasan of consumer have an effect on by signifikan to decision of transfer of brand can be accepted. Result of characteristic regresi coefficient categorize product 0,235 and signifikan level 0,009 < 0,05 second so that characteristic categorize product have an effect on by signifikan to decision of transfer of brand can be accepted. Result of experience regresi coefficient to the product 0,162 and signifikan level 0,036 < 0,05 so that third hypothesis of Experience to the product have an effect on by signifikan to decision of transfer of brand can be accepted. Result of F calculate equal to 35,494 and signifikan storey;level 0,000 < 0,05 so that there is positive influence and signifikan between ketidakpuasan of consumer, characteristic categorize product, experience to the product to decision of transfer of brand. Equal to 51,1 % decision of transfer of brand can be explained by disgruntled of consumer, characteristic categorize product, experience to the product. While the rest 48,9% explained by other causes outside variable disgruntled of consumer, characteristic categorize product, experience to the product.